The effect of sulthiame on potential biomarkers in moderate to severe obstructive sleep apnoea - Erik Hoff; Saliha Musovic; Ali M. Komai; Ding Zou; Christian Strassberger; Kaj Stenlöf; Ludger Grote; Jan Hedner (ERJ Open Research)
Background Obstructive sleep apnoea (OSA) is a common disease with breathing disturbances during sleep. Sulthiame (STM), a carbonic anhydrase (CA) inhibitor, was recently shown to reduce OSA in a significant proportion of patients. CA activity and hypoxia-inducible factor (HIF)-1α are two potential biomarkers reported in severe OSA and hypoxia. Both have been considered to play roles in the development of OSA comorbidities. This study investigated the effects of STM on these biomarkers in OSA. Methods This was an exploratory analysis of a randomised, double-blind, placebo-controlled trial of STM in OSA. Patients with moderate to severe OSA, body mass index 20–35 kg·m−2, aged 18–75 years and not accepting positive airway pressure treatment were randomised to 4 weeks with placebo, STM 200 mg or STM 400 mg. CA activity (n=43) and HIF-1α concentration (n=53) were determined at baseline, after 4 weeks of treatment and 2 weeks after treatment completion. Results In the 400 mg group, both CA activity and HIF-1α concentration were reduced (median difference −26% (95% CI −32– −12%) and −4% (95% CI −8– −2%); both p<0.05 versus placebo). The reductions were sustained 2 weeks after treatment completion. In the 200 mg group, both CA activity and HIF-1α were numerically reduced. The STM-induced reductions in CA activity and HIF-1α correlated significantly (r=0.443, p=0.023). Conclusions STM treatment in OSA induced a reduction of both CA activity and HIF-1α concentration. The effects remained 2 weeks after treatment completion, suggesting prolonged effects of STM in OSA.